2022
DOI: 10.1007/s10508-022-02458-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of First UK-Wide Lockdown (March–June 2020) on Sexual Behaviors in Men and Gender Diverse People Who Have Sex with Men During the COVID-19 Pandemic: A Cross-Sectional Survey

Abstract: The global COVID-19 pandemic resulted in strict social distancing measures restricting close physical contact. Men (cis and trans) and other gender diverse people who have sex with men (MGDSM) are at higher risk of sexually transmitted infections (STIs) and may have experienced changes in sexual behavior during government restrictions on social and sexual contact. We aimed to examine self-reported sexual behavior of MGDSM during the first UK-wide lockdown to identify the characteristics of the individuals who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The authors highlight the role of remote testing services, which were limited in Ireland at the time, underlining the role of service diversification in responding to shocks. Another UK study found that sub-groups of men and gender diverse people who have sex with men maintained or increased sexual behaviour, and (in contrast with our results) that younger people were more likely to have sexual health need during the early stages of the COVID-19 crisis [ 6 , 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The authors highlight the role of remote testing services, which were limited in Ireland at the time, underlining the role of service diversification in responding to shocks. Another UK study found that sub-groups of men and gender diverse people who have sex with men maintained or increased sexual behaviour, and (in contrast with our results) that younger people were more likely to have sexual health need during the early stages of the COVID-19 crisis [ 6 , 40 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The restrictions on social gatherings–which included limits on wedding attendance ( Fig 1 )–together with the negative economic impact of the epidemic, probably explain the observed reductions in young females’ marriage and onset of sexual activity. For males, our finding of only a short-lived reduction in SRB early in the Covid-19 epidemic matches results from studies of MGDSM in high income countries [ 15 17 ].…”
Section: Discussionsupporting
confidence: 88%
“…Much of the existing evidence is focused on men (cis and trans) and other gender-diverse people who have sex with men (MGDSM) populations in high-income countries with the general finding that risk behaviours, or sexual activity more broadly, declined dramatically early on in the Covid-19 pandemic in 2020 [ 15 17 ]. One study examined changes to sexual risk behaviour amongst the general population in Panama, with 28.8% of participants reporting a decrease in casual sex and 68.6% reporting no change [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes to sexual behaviour have been reported among GBMSM in the UK during periods of COVID-19 restrictions, however, there has been limited evidence exploring behavioural modification in response to the 2022 mpox outbreak. While sexual mixing outside of households generally persisted through COVID-19 pandemic waves (19,23), studies noted swift rebounds in sexual risk behaviour following easing of social restrictions (18). Our findings support other evidence of behavioural modification among GBMSM during the mpox outbreak, as UK surveillance data show a concurrent, but temporary decline in lymphogranuloma venereum (LGV) and Shigella species, infections that primarily circulate in the dense, interconnected sexual networks associated with mpox transmission (10, 24).…”
Section: Discussionsupporting
confidence: 72%